PENGGUNAAN MEDIA POSTER UNTUK MENINGKATKAN MINAT BACA DI KALANGAN MAHASISWA - Iwan Fahmi Faturochman (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
This research is based on the lack of knowledge and the use of poster media in increasing reading interest among students. in connection with the development of print media. So, directly forcing to sharpen the observation of the information in circulation. This, causes that the progress of print media or science and technology affects the development of literacy. For this reason, poster media is a means of increasing the attractiveness of reading and providing significant changes for literacy advancement. Thus, poster media must provide different changes specifically for students to be more interested in reading interest. In addition, poster media provide encouragement and motivation as a driving force, a guide in a good direction. As for this study, the researcher wanted to know how much influence the poster media had to increase reading interest among students. This study uses a qualitative descriptive method that describes data and facts in the form of descriptions obtained through processing and collecting data through a questionnaire distributed via WhatsApp. The sample of this research was conducted on 10 students of IKIP Siliwangi in various departments. The results of this study of 9 people gave the answer that poster media made increased attractiveness in literacy and there were 7 people affected by poster media by giving answers, that posters were persuasive, which meant to attract attention by unifying images, writing colors, and words.